KEPEMIMPINAN KRISTEN DALAM BUDAYA PATRIARKIMengeksplorasi Narasi Terhadap Figur Pemimpin Perempuan Dalam Alkitab Seperti Debora, Ester, Miryam Sebagai Landasan Servant Leadership - Damaris Rumba; Firdayanti Talle’; Lita Bungan; Meriati Tudang; Risa Pangari (CV. ADIBA AISHA AMIRA, 2025)
This study examines the figures of female leaders in the Bible, such as Deborah, Esther, and Miriam, as the foundation for the concept of